2021
DOI: 10.3390/ani11030727
|View full text |Cite
|
Sign up to set email alerts
|

Total and Differential Cell Counts as a Tool to Identify Intramammary Infections in Cows after Calving

Abstract: Milk differential somatic cells count (DSCC), made possible under field conditions by the recent availability of a high-throughput milk analyzer may represent an improvement in mastitis diagnosis. While an increasing number of studies reports data on DSCC on individual cow samples, very few concerns DSCC from quarter milk samples. This paper reports for the first time the results of a retrospective study aiming to assess the performance of total (SCC), DSCC, and a novel calculated marker (PLCC) measured on qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…The software determines the best decision to make at each decision node. Once the decision tree is complete, it creates a full decision analysis statistics report and its comparison with alternative decisions, as reported in studies in human and veterinary diagnostics [31,32]. The input values for this analysis are reported in Table 1.…”
Section: Decision-tree Analysismentioning
confidence: 99%
“…The software determines the best decision to make at each decision node. Once the decision tree is complete, it creates a full decision analysis statistics report and its comparison with alternative decisions, as reported in studies in human and veterinary diagnostics [31,32]. The input values for this analysis are reported in Table 1.…”
Section: Decision-tree Analysismentioning
confidence: 99%
“…According to Zecconi et al . (2018, 2021), DSCC allows for a more accurate detection of subclinical mastitis implementing the information provided by SCC. Currently, the SCC is used for different purposes, such as for the milk payment systems, to check compliance with regulations in terms of milk quality and hygienic standard, and in milk recording for genetic evaluation and farm management (IDF 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers suggest that DSCC should be coupled with other routinely available milk data, such as SCS, pH, lactose content, and electrical conductivity [23][24][25]. The PMN S proposed in this study seems a more precise indicator of udder health compared to DSCC, as it simultaneously provides information about total SCC and those fractions known to be predominant during mastitis [11,20]. Commonly, suspicious cows or quarters are reported to show milk SCC ≥ 200,000 cells/mL and at the same time DSCC equal or greater than 0.65 [10,20,26]; it derives that a potential accurate PMN threshold approximately corresponds to 130,000 cells/mL and that cows whose milk present PMN above this value might thus be monitored.…”
Section: Fixed Effectsmentioning
confidence: 96%
“…Several research articles investigated the effect of DCT on healthy quarters milk SCC, but without looking at differences in detailed SCC fractions, namely macrophages, neutrophils, and lymphocytes. A better understanding of changes in SCC fractions is important, as it has been demonstrated that only neutrophils and lymphocytes are elevated in high-SCC milk and/or in mastitic milk [9][10][11]. Compared to the conventional total SCC, neutrophils and lymphocytes could be more informative of the mammary gland health status [1].…”
Section: Introductionmentioning
confidence: 99%